Molecular interaction of patchouli extraction process using molecular dynamic simulation approach - Siti Hana, Abu Bakar (2014)
Patchouli is one of the native commercial crops in Malaysia which has various applications in the fragrances and cosmetics industries as well as in alternative medicine area. These are due to the interesting pharmacological properties and aroma of its essential oil. Currently, patchoulol, a marker compound is still not produced synthetically. The demand for patchouli essential oil will increase as patchoulol has been found to possess antiviral property specifically towards H1N1 virus. This study aims to recognise the intermolecular interaction during the patchouli extraction process through the application of molecular dynamics simulation and explaining the process at molecular scale with the extraction yield as a correlation. Therefore this study is focussed on the solvent extraction experiment and molecular dynamic simulation. Simulation works comprise comparison between hydro-distillation and solvent extraction techniques with three types of solvents; the polar protic, polar aprotic and non-polar solvents. The temperature variation effect on solvent extraction is also simulated. Results suggest that a polar protic solvent of ethanol can establish a higher degree of hydrogen bonding and produce the highest extraction yield (30.99% wt/wt) which suggested a good correlation. Meanwhile an interesting finding is that hexane as non-polar solvent managed to shift the O1P---H1P interaction up to 5.75Å from 1.75Å in pure patchoulol system and extracted patchouli oil in higher yields compared to polar aprotic solvent of acetone. The molecular dynamics simulation work revealed that there is repulsion between O1A---O1P atom which may retard the solute solubility and produced the lowest extraction yield. The molecular dynamics simulation enable visualisation of the hydrophobic character of the patchoulol compared to well distribute solute in the ethanol solvent extraction binary system. The temperature variation effect study found that the small temperature increment of 5K may be the reason for a slight perturbation in the interaction structure which was captured by the molecular dynamics simulation.